2013
DOI: 10.1063/1.4795296
|View full text |Cite
|
Sign up to set email alerts
|

On the stochastic excitation of monostable and bistable electroelastic power generators: Relative advantages and tradeoffs in a physical system

Abstract: Numerical and experimental investigations of broadband random vibrational energy harvesting using monostable and bistable piezoelectric cantilevers are presented along with relative performance comparisons. Simulations and experiments reveal that a linear-monostable energy harvester can outperform its bistable counterpart for very low and relatively high random excitation levels. The bistable configuration generates more power for a limited excitation intensity range slightly above the threshold of interwell o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 26 publications
6
63
0
Order By: Relevance
“…Cottone et al [11] and Daqaq [12] showed that when driven by white noise, a necessary condition for the bistable harvester to outperform its linear counterpart is to have a small ratio of mechanical to electrical time constants. They along with other researchers [13,14,15] showed that for a given noise intensity, the output power highly depends on the shape of the bistable potential. Zhao and Erturk [15] showed that the bistable harvester could outperform its linear counterpart only in a narrow region where noise intensity is slightly above the threshold of interwell oscillations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cottone et al [11] and Daqaq [12] showed that when driven by white noise, a necessary condition for the bistable harvester to outperform its linear counterpart is to have a small ratio of mechanical to electrical time constants. They along with other researchers [13,14,15] showed that for a given noise intensity, the output power highly depends on the shape of the bistable potential. Zhao and Erturk [15] showed that the bistable harvester could outperform its linear counterpart only in a narrow region where noise intensity is slightly above the threshold of interwell oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…They along with other researchers [13,14,15] showed that for a given noise intensity, the output power highly depends on the shape of the bistable potential. Zhao and Erturk [15] showed that the bistable harvester could outperform its linear counterpart only in a narrow region where noise intensity is slightly above the threshold of interwell oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…The noise distribution is usually modelled as Gaussian. White Gaussian stochastic excitation on linear and non-linear harvesters have been considered in a number of theoretical, numerical and experimental investigations 8,9,10,11,12,13 and the overall outcome have been formulated recently by Halvorsen 12 as "nonlinear harvesters are not fundamentally better than linear ones", but nonlinear harvesters can be tuned to out-perform linear ones if the intensity of white noise is known and fixed. On the contrary, harmonic form is characterised by a single delta-peak in the spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] To overcome the narrow bandwidth problem, the multi-modal oscillators 4 and the frequencytuning scheme 5 were proposed to expand the bandwidth. Specially, many researchers have extensively studied the performance improvement achieved by introducing nonlinear dynamic behaviors such as mono-stable, 6,7 bi-stable, [8][9][10][11][12][13][14] tri-stable 15,16 and impact 17 to vibration energy harvesters. Gafforelli et al 18 experimentally investigated the mono-stable Duffing oscillator with a doubleclamped beam.…”
Section: Introductionmentioning
confidence: 99%